The Effectiveness of Gamification Strategy on English Vocabulary Enhancing at SDN Ngronggo 8 Kediri - Sarbanun Tuanany; Erwin Hari Kurniawan; M. Syaichul Muchyidin (Universitas Cokroaminoto Palopo, 2025)
This study examines the effectiveness of Blooket media in enhancing English vocabulary among students. A quantitative research approach was employed, utilizing a pre-experimental design with a single group pre-test and post-test. The participants included 31 fifth-grade students from SDN Ngronggo 8 Kediri during the 2024/2025 academic year. The findings revealed that the average pre-test score was 67.25, while the post-test score increased to 81.61, indicating a marked improvement. Statistical analysis using a paired sample t-test yielded a significance value (2-tailed) of 0.001, which is less than the threshold of 0.05, confirming a significant increase in vocabulary performance. These results demonstrate that the implementation of Blooket media effectively enhances students' English vocabulary learning.